Using Combined One-Time Password for Prevention of Phishing Attacks - Nasiri, S.; Tahghighi Sharabian, M.; Aajami, M. (Engineering, Technology & Applied Science Research, 2017)
Αs technologies and communications develop, more sabotaging attacks occur including phishing attacks which jeopardize users’ security and critical information like their passwords and credentials. Several solutions have been proposed for existing dangers. One of which is the use of one-time passwords. This issue has remained as a main challenge and requires more extensive research. In this research, we have focused on one-time password combinations and we also have proposed solutions based on behavioral patterns which lead to significant optimizations while tending the simplicity for users. Efficiency of the proposed method has been measured through defining scenarios, modeling and simulations based on a prevention rate index. In addition, complexity coefficient of the proposed method showing the probability of unpredictability of passwords for attackers has been calculated. Ultimately, a descriptive comparison has shown that the proposed method is superior to some of the existing methods.